The efficiency of polysaccharide microencapsulation in improving survival of probiotic bacteria - Prasit Khumpouk; Napatsakorn Saichanaphan; Umaporn Khimmakthong (Songklanakarin Journal of Science and Technology (SJST), 2022)
The objective of this research was to find polysaccharides for encapsulating B. subtilis to achieve the highest survival in low pH conditions. In the experiment, Bacillus subtilis were encapsulated in gelatin together with alginate and chitosan (GACh), carrageenan together with alginate and chitosan (CACh), or tapioca starch together with alginate and chitosan (SACh). The results showed that SACh encapsulation had the most effective B. subtilis release from gel beads. When testing for B. subtilis survival at pH 2, the SACh encapsulated B. subtilis had the highest percent survival. The survival of B. subtilis in SACh when stored at -18, 0, 4, 10, and 25 ºC was evaluated and the results show that 4 ºC is the most suitable storage temperature for the gel beads. In a test of encapsulated B. subtilis stored at 4 ºC, B. subtilis in SACh had the highest survival rate.